Cured product, curable resin composition, and method for producing the cured product
A biodegradable cured product with glycidic acid ester groups is created, addressing toxicity and decomposition issues of epoxy resins by enabling easy dismantling and environmental safety through alkaline or enzymatic decomposition.
Patent Information
- Application Number
- JP2020060240
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-03-30
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-03-30
AI Technical Summary
Existing epoxy resins pose environmental and health hazards due to toxicity and difficulty in decomposition, and there is a need for biodegradable adhesives that can be easily dismantled and recycled.
A cured product is developed using a reactive composition containing glycidic acid ester groups, which can be decomposed by alkaline or lipase-containing aqueous solutions, and is produced through a process involving the polymerization of specific epoxy compounds with glycidic acid ester groups.
The cured product exhibits high degradability, allowing it to be decomposed by alkaline or enzymatic means, and can be cured at room temperature with amine compounds or provide excellent hardness with acid anhydrides, suitable for applications requiring easy dismantling and reduced environmental impact.
Smart Images

Figure 0007616629000001 
Figure 0007616629000002 
Figure 0007616629000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a cured product, specifically, a cured product of an epoxy compound having one or more glycidic acid ester groups, which is decomposable by an alkaline aqueous solution or an aqueous solution containing lipase. [Background technology]
[0002] Epoxy resins are used for various purposes, but there are concerns about their toxicity to the environment and living organisms, as they can cause allergic symptoms such as dermatitis. In particular, various studies are being conducted on glycidyl ether-type bisphenol A epoxy resins to prevent health damage. Glycidyl ester-type epoxy resins such as diglycidyl phthalate have improved safety compared to glycidyl ether-type epoxy resins, but further safety improvements are necessary. In addition, thermosetting resins such as bisphenol A epoxy resins are generally difficult to decompose. For example, adhesives using epoxy resins peel off again once they are bonded, and are not easy to dismantle, which is a major issue from the perspective of resource recycling. For this reason, there is an increasing demand for dismantlable materials such as easily dismantlable adhesives that can be easily peeled off and dismantled after use.
[0003] In addition, the demand for biodegradable resins is increasing in order to reduce the burden on the environment. However, the only resins that have been confirmed to be biodegradable at the same rate as food waste from ordinary households are thermoplastic resins such as aliphatic polyesters and aliphatic polyamides.
[0004] Patent Document 1 describes the epoxidation of the acrylic acid functional groups of a compound containing multiple acrylic acid functional groups to produce an epoxy resin prepolymer containing multiple glycidic acid functional groups, which is less toxic than glycidyl ether-type epoxy resins. Patent Document 2 describes a cured product of a reactive composition containing a specific ratio of glycidic acid ester groups and acrylate groups, which can have a glass transition temperature that can be adjusted arbitrarily. However, the biodegradability of these resins is unknown. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2015-214497 A [Patent Document 2] JP 2019-196315 A Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a degradable cured product. [Means for solving the problem]
[0007] The inventors have found that a degradable cured product can be obtained by polymerizing a reactive composition containing a glycidic acid ester group, and have completed the present invention.
[0008] That is, the present invention relates to a compound represented by the following general formula (Ia): [ka] (In general formula (Ia), R 1 , R 2 , and R 3 are each independently a monovalent group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, and a phenyl group. The present invention relates to a cured product of an epoxy compound having one or more glycidic acid ester groups represented by the following formula (1):
[0009] It is preferable that the epoxy compound has two or more glycidic acid ester groups.
[0010] The present invention also relates to a curable resin composition for producing the cured product.
[0011] The curable resin composition preferably contains a curing agent.
[0012] The curing agent is preferably an amine-based curing agent or an acid anhydride.
[0013] The curable resin composition preferably contains a curing accelerator.
[0014] The present invention also relates to a method for producing a cured product, which comprises a step of heating the curable resin composition at 120° C. or lower. Effect of the Invention
[0015] The cured product of the present invention has high decomposability. In addition, when an amine compound is used as the curing agent, the product can be cured at room temperature, and when an acid anhydride is used, a cured product with excellent hardness can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] <<Cured product>> The present invention relates to a compound represented by the following general formula (Ia): [ka] (In general formula (Ia), R 1 , R 2 , and R 3 are each independently a monovalent group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, and a phenyl group. The present invention relates to a cured product of an epoxy compound having one or more glycidic acid ester groups represented by the following formula (1):
[0017] In the general formula (Ia), R 1 , R 2 , R 3 are each independently a hydrogen atom, C 1-6 From the viewpoints of availability of the raw material compounds and ease of the curing reaction, R 1 is methyl and R 2 and R3 is a hydrogen atom, or R 1 , R 2 , R 3 It is preferable that all of these are hydrogen atoms.
[0018] The cured product of the present invention has high degradability. Here, degradability means that the cured product can be decomposed or its physical properties can be deteriorated by the action of an alkaline aqueous solution or an aqueous solution containing lipase.
[0019] <Epoxy compounds> The epoxy compound having one or more glycidic acid ester groups is represented by the following general formula (II): (Ia) m -A: (II) It is expressed by:
[0020] In the general formula (II), m is the number of glycidic acid ester groups in the epoxy compound. m is 1 or more, but is preferably 2 or more from the viewpoint of decomposability of the cured product. The upper limit of m is not particularly limited, but is usually about 4. The number of carbon atoms in the organic group A is preferably 1 to 20, more preferably 1 to 10, from the viewpoint of ease of handling when curing as a resin and ease of curing reaction. The organic group A has a saturated or unsaturated hydrocarbon group as its main skeleton, and the hydrocarbon group may have either a branched or linear structure, or the skeleton of the hydrocarbon group may have a cyclic structure, such as a 1,4-cyclohexylene group. The organic group A may also have heteroatoms such as N, S, and O in the molecular chain. The methylene groups other than the terminals in the organic group may be replaced with 1 to 4 heteroatoms selected from NH, S, and O, or an arylene group or a heteroarylene group. The hydrogen atoms in the organic group may be substituted with hydroxy, cyano, amino, nitro, halogen, or phenyl.
[0021] Examples of the organic group A include linear hydrocarbons such as methylene, ethylene, propylene, butylene, pentylene, hexylene, heptylene, octylene, and nonylene, branched hydrocarbons such as 2,2-dimethylpropylene and 2-ethyl-2-methylpropylene, cyclic hydrocarbons such as 1,4-cyclohexylene, sugars, PEG chains, and further trivalent or tetravalent groups of these groups. Of these, nonylene and 2,2-dimethylpropylene are preferred.
[0022] The epoxy compound having a glycidic acid ester group preferably has an epoxy equivalent of not more than 1000, more preferably not more than 750. If the epoxy equivalent exceeds 1000, crosslinking becomes insufficient, and various physical properties of the cured product tend to deteriorate.
[0023] From the viewpoint of reducing toxicity to living organisms, it is desirable to have the epoxy group contained in the compound as a glycidic acid ester group, but it is also possible to have a part of the glycidic acid ester group have a glycidyl ether or glycidyl ester structure depending on the application, etc.
[0024] As long as the epoxy compound has one or more glycidic acid ester groups, it may contain an alcohol or diol that is a hydrolysis product at the ester or epoxy group portion, or pyruvic acid that is an isomerization product of the epoxy group.
[0025] In the epoxy compound of the general formula (II), the organic group A may further include a group represented by the following general formula (Ib): [ka] The structure R 1 is as defined for general formula (Ia). 4 , and R 5 R is each independently a monovalent group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, and a phenyl group. 4 is R in general formula (Ia) 2 is the same as R 5 is R in general formula (Ia) 3Preferably, R 4 is R in general formula (Ia) 3 is the same as R 5 is R in general formula (Ia) 2 It is preferable that the ratio is the same as
[0026] When the structure of general formula (Ib) is bonded to the organic group A, the epoxy compound has the following general formula (III): (Ia) m -A-(Ib) n (III) n represents the number of (meth)acrylic acid ester groups in the molecule and is an integer of 0 to 6. m+n is 2 to 6, preferably 2 to 4, more preferably 2 or 3, and most preferably 2.
[0027] In the epoxy compound represented by general formula (III), the molar ratio of the structure represented by formula (Ia) to the structure represented by formula (Ib) is preferably (Ia):(Ib)=99:1 to 95:5, more preferably 99:1 to 96:4. If the ratio of formula (Ia) is less than 95, the decomposition property tends to decrease. The molar ratio of the structure represented by formula (Ia) to the structure represented by formula (Ib) in the composition can be determined by measurement using 1H-NMR.
[0028] The epoxy compound having one or more glycidic acid ester groups represented by the general formula (II) is represented by the general formula (IV): [ka] (In general formula (IV), A, R 1 , R 4 and R 5 is as defined above. k indicates the number of structures in the parentheses. It can be produced by oxidizing the carbon-carbon double bond of a compound represented by the formula (IV) with an oxidizing agent and converting it to an epoxy group. In the general formula (IV), k is 2 to 6, preferably 2 to 4, more preferably 2 to 3, and most preferably 2.
[0029] Examples of the compound represented by the general formula (IV) include neopentyl glycol diacrylate, 1,9-bisacryloyloxynonane, 1,6-bisacryloyloxyhexane, tricyclo[5.2.1.0 2,6 ] Decanedimethanol diacrylate, polyethylene glycol diacrylate, and trimethylolpropane triacrylate are examples.
[0030] The reaction for obtaining the epoxy compound of general formula (II) from the compound of general formula (IV) can be carried out without using a solvent, particularly an organic solvent which is accompanied by problems of disposal and separation, but in some cases, it can be carried out using an organic solvent. It can also be carried out in an aqueous medium, for example, in the presence of a buffer solution. It is preferable to carry out the reaction in a buffer solution, since it is possible to achieve a good conversion rate without decomposing the ester structure of the epoxy compound of general formula (II). There is no particular restriction on the type of buffer solution, and any solution known to those skilled in the art can be used as long as it does not inhibit the epoxidation reaction. An example of a preferred buffer solution is an aqueous sodium bicarbonate solution (pH 8.2).
[0031] A phase transfer catalyst may be used in the reaction of obtaining an epoxy compound of general formula (II) from a compound represented by general formula (IV). Examples of the phase transfer catalyst include quaternary ammonium salts such as trioctylmethylammonium chloride, tributylbenzylammonium chloride, tetrabutylammonium iodide, tetrabutylammonium chloride, tetrabutylammonium bromide, tetramethylammonium chloride, tetraoctylammonium bromide, tetraheptylammonium bromide, and tetrahexylammonium bromide, sulfobetaines such as lauryl sulfobetaine, laurylhydroxysulfobetaine, myristylsulfobetaine, palmitylsulfobetaine, and stearylsulfobetaine, and organic acid salts such as sodium lauryl sulfate, sodium dodecylbenzenesulfonate, and potassium oleate. Among these, ammonium salts with a suitable carbon chain length such as tetraoctylammonium bromide and tetraheptylammonium bromide, and laurylsulfobetaine are preferred. The phase transfer catalyst is used in an amount of 1 to 100 mol % based on the epoxy compound of the general formula (II).
[0032] In the reaction to obtain an epoxy compound of general formula (II) from a compound of general formula (IV), an oxidizing agent that converts the carbon-carbon double bond in the compound of general formula (IV) to an epoxy group is used. The oxidizing agent can be appropriately selected from known oxidizing agents, and examples thereof include sodium hypochlorite, potassium hypochlorite, calcium hypochlorite, ammonium hypochlorite, hydrogen peroxide (water), peracetic acid, m-chloroperbenzoic acid, perbenzoic acid, t-butyl hydroperoxide, oxone, metal oxides (vanadyl acetylacetonate, etc.), ammonium hypobromite, calcium hypobromite, potassium hypobromite, and sodium hypobromite. Among them, water-soluble salts such as sodium hypochlorite and sodium hypobromite are preferred. The oxidizing agent is preferably used in an amount of 1 to 5 equivalents, more preferably 1.2 to 3 equivalents, relative to the olefin in the compound of general formula (IV). The molar ratio of the structures represented by general formulae (Ia) and (Ib) in the entire composition can be adjusted by adjusting the reaction temperature, reaction time, and also the amount of the oxidizing agent.
[0033] In the reaction for obtaining the epoxy compound of general formula (II) from the compound of general formula (IV), the atmosphere during the reaction is not particularly limited, and the reaction may be carried out in an inert atmosphere such as argon or nitrogen, or in air at atmospheric pressure. The reaction temperature and reaction time vary depending on the type of substrate used, but the reaction is usually carried out under conditions of, for example, 35 to 45°C and 0.5 to 2 hours.
[0034] When obtaining the epoxy compound of general formula (II), a diol in which the epoxy group in the compound of formula (IV) is hydrolyzed, or an alcohol in which the ester bond is hydrolyzed may be by-produced, and a pyruvic acid derivative may be formed by isomerization of the epoxy group. The epoxy compound in the present invention may contain these impurities within a range that does not impair the effects of the present invention. These impurities can be removed as necessary by a method known to those skilled in the art, such as silica gel chromatography.
[0035] In the epoxy compound of general formula (II), when the structure of general formula (Ib) is further bonded to the organic group A, it is preferable to carry out a radical polymerization reaction using the structure of general formula (Ib) before subjecting the epoxy compound to a curing reaction. Examples of initiators used in radical polymerization include 2,2'-azobispropane, 2,2'-dichloro-2,2'-azobispropane, 1,1'-azo(methylethyl)diacetate, 2,2'-azobis(2-amidinopropane) hydrochloride, 2,2'-azobis(2-aminopropane) nitrate, 2,2'-azobisisobutane, 2,2'-azobisisobutyric acid, 2,2'-azobisisobutyronitrile, 2,2'-azobis-2-methyl methylpropionate, 2,2'-dichloro-2,2' -Azobisbutane, 2,2'-azobis-2-methylbutyronitrile, 2,2'-azobisisobutyric acid dimethyl, 1,1'-azobis(1-methylbutyronitrile-3-sodium sulfonate, 2-(4-methylphenylazo)-2-methylmalonodinitrile, 4,4'-azobis-4-cyanovaleric acid, 3,5-dihydroxymethylphenylazo-2-allylmalonodinitrile, 2,2'-azobis-2-methylvaleronitrile, 4,4'-azobis-4-cyanovaleric acid dimethyl, 2,2'-azobis 2,4-dimethylvaleronitrile, 1,1'-azobiscyclohexanenitrile, 2,2'-azobis-2-propylbutyronitrile, 1,1'-azobis-1-chlorophenylethane, 1,1'-azobis-1-cyclohexanecarbonitrile, 1,1'-azobis-1-cycloheptanenitrile, 1,1'-azobis-1-phenylethane, 1,1'-azobiscumene, 4-nitrophenylazobenzyl ethyl cyanoacetate, phenylazodiphenylmethane, phenylazotriphenylmethan Azo radical polymerization initiators such as 4-nitrophenylazotriphenylmethane, 1,1'-azobis-1,2-diphenylethane, poly(bisphenol A-4,4'-azobis-4-cyanopentanoate), and poly(tetraethylene glycol-2,2'-azobisisobutyrate), acetyl peroxide, cumyl peroxide, tert-butyl peroxide, propionyl peroxide, benzoyl peroxide, 2-chlorobenzoyl peroxide, 3-chlorobenzoyl peroxide, 4-chlorobenzoyl peroxide, 2,Examples of the polymerization initiator include 4-dichlorobenzoyl, 4-bromomethylbenzoyl peroxide, lauroyl peroxide, potassium persulfate, diisopropyl peroxycarbonate, tetralin hydroperoxide, 1-phenyl-2-methylpropyl-1-hydroperoxide, tert-butyl triphenylacetate, tert-butyl hydroperoxide, tert-butyl performate, tert-butyl peracetate, tert-butyl benzoate, tert-butyl perphenylacetate, tert-butyl per-4-methoxyacetate, and tert-butyl per-N-(3-tolyl)carbamate. Examples of the polymerization initiator include peroxide radical polymerization initiators such as benzoyl peroxide, lauroyl peroxide, cumene hydroperoxide, t-butyl hydroperoxide, di-t-butyl peroxide, and methyl ethyl ketone peroxide. These may be used alone or in combination of two or more.
[0036] The amount of the initiator to be added is preferably 0.1 to 10 mol %, more preferably 0.5 to 3 mol %, based on the reactive composition.
[0037] The reaction temperature, reaction time, and the presence or absence of light irradiation in the radical polymerization reaction are not particularly limited, but the reaction can be carried out under conditions of, for example, room temperature to 90° C. and 30 seconds to 18 hours.
[0038] When the epoxy compound of the present invention contains a (meth)acrylic acid ester group, the epoxy compound is soluble in one or more solvents selected from the group consisting of esters, halogen-containing solvents, ethers, ketones, amides, aromatics, alcohols, dimethyl sulfoxide, and mixtures thereof, and can be suitably used for applications such as adhesives and coatings. Specific examples of such solvents include esters such as ethyl acetate, butyl acetate, ethylene glycol monomethyl ether acetate, propylene glycol methyl ether acetate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, glycidyl methacrylate, methyl acrylate, ethyl acrylate, and butyl acrylate; halogen-containing solvents such as chloroform, dichloromethane, and chlorobenzene; ethers such as tetrahydrofuran, 1,4-dioxane, diglyme, tetraglyme, propylene glycol monomethyl ether, propylene oxide, phenyl glycidyl ether, and bisphenol A diglycidyl ether; ketones such as acetone, ethyl methyl ketone, and cyclohexanone; amides such as dimethylformamide, dimethylacetamide, and N-methylpyrrolidone; aromatics such as toluene and xylene; alcohols such as ethanol, propanol, and ethylene glycol; dimethyl sulfoxide, and mixtures thereof. The solubility of an epoxy compound in a solvent can be measured by the presence or absence of precipitation when the epoxy compound is added to a solvent to give a given concentration (for example, 0.5% by weight). If no precipitation occurs, the epoxy compound is determined to be soluble.
[0039] When a radical polymerization reaction is carried out, the epoxy compound of the present invention may be copolymerized with other monomers. Examples of the monomers to be copolymerized include alkyl esters of (meth)acrylic acid having 1 to 18 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; hydroxyl group-containing (meth)acrylic acid esters, such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate; dimethacrylate; and the like. nitrogen-containing (meth)acrylic esters such as ethylaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate; other (meth)acrylic esters such as glycidyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, morpholyl (meth)acrylate, isobornyl (meth)acrylate and cyclohexyl (meth)acrylate; styrenes such as styrene, p-acetoxystyrene, chloromethylstyrene, p-methylstyrene and divinylbenzene, vinyl acetate, acrylonitrile, maleic anhydride, and thiols.
[0040] <Degradability> The cured product of the present invention is a cured product of an epoxy compound having a glycidic acid ester group, and therefore can be decomposed or have its physical properties deteriorated by an alkaline aqueous solution or an aqueous solution containing lipase.
[0041] The decomposability in an alkaline aqueous solution is measured by placing a test piece made of a cured product measuring 5 mm x 5 mm x 1 mm in a 1M NaOH aqueous solution (pH 14) at 37°C. If the test piece completely dissolves within 10 days under these conditions, it is considered to be decomposable in an alkaline aqueous solution. The number of days until the test piece is completely dissolved is preferably 5 days or less, more preferably 3 days or less. In addition, when the test piece is placed in a 0.1M NaOH aqueous solution (pH 13) at 37°C, the number of days until the test piece is completely dissolved is preferably 14 days or less, more preferably 10 days or less.
[0042] Decomposability in an alkaline aqueous solution can also be measured by placing a test piece of the cured product measuring 10 mm x 5 mm x 1 mm in a 1M NaOH aqueous solution (pH 14) at 60°C for 7 days. If the weight change rate under these conditions is 35% or less, the product is deemed decomposable in an alkaline aqueous solution. A weight change rate of 30% or less is preferable, and 20% or less is more preferable. Weight change rate (%) = (weight of test piece after test) ÷ (weight of test piece before test) × 100
[0043] The decomposability by a lipase-containing aqueous solution is measured by placing a test piece made of a hardened material measuring 5 mm x 5 mm x 1 mm in an aqueous solution containing lipase at a concentration of 140 U / ml at 37°C. If the test piece swells or dissolves within 90 days under these conditions, it is considered to be decomposable by a lipase-containing aqueous solution. The number of days until the test piece is completely dissolved is preferably 90 days or less, more preferably 28 days or less, and even more preferably 21 days or less. Here, the unit of lipase is defined as 1U, which is the amount of enzyme that hydrolyzes 1.0 microequivalent of triglyceride to fatty acid at pH 7.2, 37°C, and 1 hour.
[0044] In addition, from the viewpoint of application as an easily dismantlable material, the cured product of the present invention may have a property of deteriorating in physical properties due to changes in appearance such as swelling or whitening, even if it does not dissolve. In this case, the deterioration in physical properties can be evaluated based on the swelling rate and the presence or absence of changes in appearance. In the case of swelling, the number of days until the swelling rate exceeds 110% is preferably within 90 days, more preferably within 31 days. Swelling ratio (%) = (weight of test piece after test) ÷ (weight of test piece before test) × 100 The whitening of the test piece indicates the onset of swelling, and the shorter the number of days, the faster the decomposition.
[0045] The cured product of the present invention may be decomposable by an acidic aqueous solution. When the product is decomposable by an acidic aqueous solution, the decomposition conditions can be selected more widely. The decomposability by an acidic aqueous solution is measured by placing a test piece of the cured product having a size of 10 mm x 5 mm x 1 mm in a 1M HCl aqueous solution (pH 0) at 60°C. If the test piece completely dissolves within 30 days under these conditions, the product is deemed decomposable by an acidic aqueous solution. The number of days until the test piece completely dissolves is preferably 28 days or less, more preferably 21 days or less. In addition, when the test piece is placed in a 0.1M HCl aqueous solution (pH 1) at 37°C, the number of days until the test piece completely dissolves is preferably 60 days or less, more preferably 50 days or less.
[0046] The cured product of the present invention may have a property of being difficult to decompose in an acidic aqueous solution, in which case the cured product of the present invention can be suitably used even under acidic conditions.
[0047] <<Curable resin composition>> The curable resin composition of the present invention is for producing the above-mentioned cured product. The curable resin composition preferably contains the above-mentioned epoxy compound and a curing agent.
[0048] <Hardening agent> The curing agent is not particularly limited as long as it is a curing agent that can be used to harden an epoxy resin, and examples thereof include amine-based curing agents, acid anhydrides, phenol-based curing agents, thiol-based curing agents, carboxylic acids, and alcohol-based curing agents.
[0049] Examples of the amine curing agent include ethylenediamine, diethylenetriamine, triethylenetetramine, N,N'-bis(3-aminopropyl)ethylenediamine, tetraethylenepentamine, pentaethylenehexamine, metaphenylenediamine, 4,4'-diaminodiphenylmethane, diaminodiphenylsulfone, m-xylylenediamine, m-xylylenediamine, propylamine, isophoronediamine, piperazine, N-aminoethylpiperazine, 1,3-bisaminomethylcyclohexane, dicyandiamide, polyamine epoxy resin adducts synthesized by reacting an epoxy resin with an excess of polyamine, ketimines, and polyamide resins synthesized by condensation of dimer acid and polyamine. Among these, in order to impart appropriate water resistance and decomposability to the cured product, highly hydrophobic amine-based curing agents and bifunctional or higher amine-based curing agents are preferred, isophoronediamine, 1,3-bisaminomethylcyclohexane, diethylenetriamine, and N,N'-bis(3-aminopropyl)ethylenediamine are more preferred, and isophoronediamine, 1,3-bisaminomethylcyclohexane, and combinations of these with other amine-based curing agents are even more preferred. Two or more amine-based curing agents may be used in combination, and in that case, it is preferred that the proportion of the amine-based curing agent with the highest hydrophobicity in the total amount of the amine-based curing agents is greater than that of the other amine-based curing agents.
[0050] Examples of the carboxylic acid include phthalic acid, maleic acid, trimellitic acid, pyromellitic acid, hexahydrophthalic acid, methyltetrahydrophthalic acid, dodecylsuccinic acid, 4-methylcyclohexane-1,2-dicarboxylic acid, 3-methyl-hexahydrophthalic acid, 4-methyl-hexahydrophthalic acid, a mixture of 3-methyl-hexahydrophthalic acid and 4-methyl-hexahydrophthalic acid, tetrahydrophthalic acid, nadic acid, methylnadic acid, norbornane-2,3-dicarboxylic acid, methylnorbornane-2,3-dicarboxylic acid, etc. Examples of the acid anhydride include anhydrides of the above-mentioned carboxylic acids.
[0051] An example of the alcohol-based hardener is polyvinyl alcohol, etc. The above hardeners may be used alone or in combination of two or more kinds.
[0052] Of the above-listed curing agents, amine-based curing agents and acid anhydrides are preferred from the viewpoint of decomposability.
[0053] The amount of the curing agent is preferably 0.5 to 1.5 times, more preferably 0.8 to 1.2 times, and even more preferably 1 times, the molar number of the curing agent functional group relative to the molar number of the epoxy group in the epoxy compound. If the amount of the curing agent is less than 0.5 times, there is a risk of poor curing due to residual epoxy groups, and if it exceeds 1.5 times, there is a risk of poor curing due to residual curing agent.
[0054] <Optional ingredients> The curable resin composition may contain, in addition to the epoxy compound and curing agent, a second epoxy compound, a filler, a curing accelerator, an organic solvent, an antifoaming agent, and the like.
[0055] The second epoxy compound is not particularly limited, and examples thereof include bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, phenol novolac type epoxy resin, alkylphenol novolac type epoxy resin, cresol novolac type epoxy resin, alicyclic epoxy resin, aliphatic chain epoxy resin, biphenyl type epoxy resin, biphenol type epoxy resin, aralkyl type epoxy resin, naphthalene type epoxy resin, dicyclopentadiene type epoxy resin, trishydroxyphenylmethane type epoxy compound, diglycidyl ether of bisphenol, diglycidyl ether of naphthalene diol, diglycidyl ether of phenols, diglycidyl ether of alcohols, triglycidyl isocyanurate, various glycidyl ether type epoxy resins, glycidyl amine type epoxy resin, glycidyl ester type epoxy resin, oxidation type epoxy resin, phosphorus modified epoxy resin, etc. These may be used alone or in combination of two or more.
[0056] When a second epoxy compound is contained, the amount of the second epoxy compound to be added can be adjusted according to the desired properties of the cured product and is not particularly limited. However, the amount is preferably 100 parts by weight or less per 100 parts by weight of the epoxy compound, so as not to impair the characteristics of the epoxy compound.
[0057] The filler is not particularly limited and may be any known filler, such as metal oxides such as silica and alumina, metal hydrates, etc. These may be used alone or in combination of two or more kinds.
[0058] When the filler is used, its content is not particularly limited, but is preferably 5 to 95% by weight, more preferably 10 to 80% by weight in the curable resin composition. If the filler content is less than 5% by weight, the thermal expansion coefficient may be high, and if it exceeds 95% by weight, the viscosity may be high and the workability may be reduced.
[0059] The curing accelerator is a compound that does not crosslink itself in the curing reaction, but accelerates the crosslinking reaction. The curing accelerator is not particularly limited and can be a known curing accelerator, for example, triphenylphosphine, imidazole, tertiary amine, etc. The imidazole is not particularly limited and can be, for example, 2-methylimidazole, 2-undecylimidazole, 2-ethyl-4-methylimidazole, 2-heptadecylimidazole, 2-phenylimidazole, 1-benzyl-2-methylimidazole, 1-cyanoethyl-2-methylimidazole, etc. The tertiary amine is not particularly limited, and examples thereof include benzylmethylamine, 2-(dimethylaminomethyl)phenol, 2,4,6-tris(diaminomethyl)phenol, triethylamine, 1,5-diazabicyclo[4,3,0]-5-nonene (San-Apro trademark: DBN), 1,8-diazabicyclo[5,4,0]-7-undecene (San-Apro trademark: DBU), DBU-phenol salt, DBU-octylate salt, DBU-p-toluenesulfonate, etc. These curing accelerators may be used alone or in combination of two or more.
[0060] When a curing accelerator is used, its content is not particularly limited, but is preferably 0.1 to 10% by weight, and more preferably 0.3 to 7% by weight, in the curable resin composition.
[0061] The organic solvent is not particularly limited, and examples thereof include N-methylpyrrolidone; N,N-dimethylformamide; dimethylsulfoxide; ketones such as methyl ethyl ketone, cyclohexanone, and cyclopentanone; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; glycol ethers such as methyl cellosolve, ethyl cellosolve, butyl cellosolve, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, diethylene glycol monoethyl ether, dipropylene glycol monoethyl ether, and triethylene glycol monoethyl ether; esters such as ethyl acetate, butyl acetate, cellosolve acetate, diethylene glycol monoethyl ether acetate, and esterified products of the above glycol ethers; alcohols such as ethanol, propanol, methanol, ethylene glycol, and propylene glycol; aliphatic hydrocarbons such as octane and decane; and petroleum solvents such as petroleum ether, petroleum naphtha, hydrogenated petroleum naphtha, and solvent naphtha. These organic solvents may be used alone or in combination of two or more.
[0062] When an organic solvent is used, its content is not particularly limited, but is preferably 20 to 300% by weight based on the solid content in the curable resin composition. If the content of the organic solvent is less than 20% by weight, the viscosity may increase, and if it exceeds 300% by weight, the curability may decrease.
[0063] The defoaming agent is not particularly limited, and examples thereof include silicones, mineral oils, polymers, etc. Examples thereof include silicones, mineral oils, polymers, etc.
[0064] When an antifoaming agent is used, its content is not particularly limited, but is preferably 0.001 to 10% by weight in the curable resin composition. If the content of the antifoaming agent is less than 0.001% by weight, antifoaming may be insufficient, and if it exceeds 10% by weight, defects may occur in the cured product or curability may decrease.
[0065] The curing conditions are not particularly limited and can be appropriately adjusted depending on the type of curing agent used. In the case of photocuring, UV, electron beam, etc. are irradiated. For example, in the case of UV irradiation, the irradiation amount is, for example, 100 to 10,000 mJ / cm. 2 The curing time can be about 100°C. As the irradiation device, for example, an ultraviolet lamp (xenon lamp, xenon mercury lamp, metal halide lamp, etc.), an arc type irradiation device, etc. can be used. In the case of thermal curing, when an amine-based curing agent is used, for example, a method of curing at room temperature for 24 hours or less, and a method of curing at 100°C for 1 to 60 minutes can be mentioned. When a carboxylic acid or its anhydride-based curing agent is used, a method of curing at room temperature to 180°C for 6 hours or less can be mentioned, and the curing temperature is more preferably 120°C or less. In applications where rapid curing is not preferred, when an amine-based curing agent is used, curing can be performed under the conditions of 6 to 12 hours at room temperature, and when a carboxylic acid or its anhydride is used, curing can be performed under the conditions of 80 to 100°C for 6 to 24 hours.
[0066] <<Application>> The uses of the cured product of the present invention include adhesives, pressure sensitive adhesives, paints, matrix resins for composite materials, casting materials, sealing materials, photoresists, etc. When the curable resin composition of the present invention is used as an adhesive or paint, it can be a one-component type or a two-component type. In the case of a two-component type, the curable resin composition and the curing agent may be separate liquids. In addition, since the cured product of the present invention is decomposable, it can also be used as an easily dismantled adhesive.
[0067] When the curable resin composition of the present invention is used as an adhesive, examples of the material to be adhered include metals such as iron, stainless steel, copper, aluminum, tinplate, and galvanized iron, polyester resins such as cycloolefin resins, polyethylene resins, polypropylene resins, and polyethylene terephthalate polybutylene terephthalate, polycarbonate resins, acrylic resins such as polymethyl methacrylate, resins such as nylon and aramid, and glass. EXAMPLES
[0068] The present invention will be described below with reference to examples, but the present invention is not limited to the following examples. In the following, "%" means "% by weight" unless otherwise specified.
[0069] (1) Materials used 1. Epoxy compounds Glycidic acid ester 1 (produced in Production Example 1) Glycidic acid ester 2 (produced in Production Example 2) Neopentyl glycol diglycidyl ether (Tokyo Chemical Industry Co., Ltd.; glycidyl ether) 2. Hardener Isophoronediamine (IPDA) (Tokyo Chemical Industry Co., Ltd.) Diethylenetriamine (DETA) (Tokyo Chemical Industry Co., Ltd.) Dodecylsuccinic anhydride (DSA) (Tokyo Chemical Industry Co., Ltd.) 4-Methylcyclohexane-1,2-dicarboxylic anhydride (MHHPA) (Tokyo Chemical Industry Co., Ltd.) Methyltetrahydrophthalic anhydride (Me-THPA) (Tokyo Chemical Industry Co., Ltd.) 3. Curing accelerator Triphenylphosphine (PPh3) (Kanto Chemical) 2-Ethyl-4-methylimidazole (EMI) (Tokyo Chemical Industry Co., Ltd.) 4. Enzymes Lipase (Sigma, derived from porcine pancreas) 5. Defoaming agents DOWSIL56Additive (Dow)
[0070] (2) Preparation of epoxy compound (Production Example 1) Glycidic acid ester 1 Neopentyl glycol diacrylate (Tokyo Chemical Industry Co., Ltd., 2.12 g, 10.0 mmol), tetrahexylammonium bromide (Tokyo Chemical Industry Co., Ltd., 1.39 g) and 5 wt% sodium hypochlorite aqueous solution (Kanto Chemical Co., Ltd., 47.6 g) were added to a recovery flask and stirred in an oil bath at 40 ° C for 1 hour. After the reaction was completed, the mixture was transferred to a separatory funnel, washed with diethyl ether (15 mL) and saturated sodium citrate aqueous solution (15 mL), and the aqueous phase was removed. The organic phase was dried over magnesium sulfate. After filtration, the mixture was purified by silica gel column chromatography with diethyl ether and hexane (volume ratio 2:1) to obtain 0.678 g (yield 27.8%) of neopenzyl glycol diglycidate as a colorless and transparent liquid.
[0071] (Production Example 2) Glycidic acid ester 2 Butyl acrylate (2.50g, 18.9mmol), benzyltributylammonium chloride (0.590g, 1.90mmol) as a phase transfer catalyst, and ethyl acetate (12.5g) were placed in a recovery flask, and 5% aqueous sodium hypochlorite solution (45.2g) was added to this mixture while stirring at room temperature, and the mixture was allowed to react with stirring for 9 hours. The reaction solution was separated, and the organic layer was washed successively with a 1% aqueous sodium thiosulfate solution and a 10% aqueous sodium sulfate solution, and the organic layer was dried over magnesium sulfate. The volatiles were removed by distillation under reduced pressure to obtain 2.32g of the target product (16.1mmol, yield 85.2%).
[0072] (3) Curing of Curable Resin Composition (Examples 1 to 9, Comparative Examples 1 to 3) An epoxy compound, a curing agent, and a curing accelerator were mixed in the weight ratios shown in Tables 1 and 2, and the mixture was degassed under vacuum to prepare a curable resin composition. For Examples 1 to 6 and Comparative Example 1, the curable resin composition was poured into a mold for test piece 1. For Examples 7 to 9 and Comparative Examples 2 and 3, the curable resin composition was poured into a mold for test piece 2. Then, the composition was cured for the curing time and at the curing temperature shown in Tables 1 and 2. Dimensions of test piece 1: 5 x 5 x 1 mm (L x W x T) Dimensions of test piece 2: 10 x 5 x 1 mm (L x W x T)
[0073] (4) Evaluation method (4-1) Glass transition temperature Measurements were performed using a Seiko Instruments DSC6200 in a nitrogen atmosphere at a heating rate of 10°C per minute. After the first heating process in which the temperature was raised from room temperature to 120°C and held for 10 minutes, the temperature was lowered to -40°C at a rate of 10°C per minute and held for 10 minutes. The midpoint of the baseline shift in the subsequent second heating process was taken as the glass transition temperature.
[0074] (4-2) Degradability (Examples 1 to 6, Comparative Example 1) The test pieces were immersed in water or various aqueous solutions listed in Table 1. The weight change of the test pieces was tracked over time, and the number of days required for the test pieces to completely dissolve was measured. Biodegradation using lipase was carried out in 0.1 M phosphate buffer (pH 7.2) at 37°C.
[0075] In addition, the test pieces were immersed in water and the weight loss rate after 24 hours was measured. Weight reduction rate (%) = ((weight of test piece before test) - (weight of test piece after test)) ÷ (weight of test piece before test) × 100
[0076] (Examples 7 to 9, Comparative Examples 2 to 3) The test pieces were immersed in water or various aqueous solutions listed in Table 2. The weight change rate after 7 days at the temperatures listed in Table 2 was measured. Biodegradation using lipase was performed in 0.1 M phosphate buffer (pH 7.2) at 37°C, the swelling rate was measured, and the number of days required for the swelling rate to exceed 110% was measured. In addition, the appearance of the test pieces was observed, and the number of days until the test pieces began to whiten was measured. If the swelling rate did not reach 110% at the time of 80 days or if no change in appearance was observed, it was determined that there was no change. The whitening of the test pieces is considered to indicate that swelling has begun, and it can be determined that the shorter the number of days until whitening begins, the faster the decomposition. Weight change rate (%) = (weight of test piece after test) ÷ (weight of test piece before test) × 100 Swelling ratio (%) = (weight of test piece after test) ÷ (weight of test piece before test) × 100
[0077] [Table 1]
[0078] As shown in Table 1, the cured product of the glycidyl ether of Comparative Example 1 did not decompose in either a lipase-containing aqueous solution or a NaOH aqueous solution. The cured products of Examples 1 to 6 did not decompose in water, but decomposed within 30 days in a lipase-containing aqueous solution and decomposed within 3 days in a 1M NaOH aqueous solution.
[0079] [Table 2]
[0080] As shown in Table 2, the weight change rate of the cured products of the glycidyl ethers of Comparative Examples 2 and 3 exceeded 35% after 7 days in a 1M NaOH aqueous solution at 60° C. The cured products of Examples 7 to 9 were completely decomposed under the same conditions.
[0081] (5) Adhesion test 1 (Examples 10 to 13, Comparative Examples 4 to 6) An adhesive composition was prepared by adding 1 weight percent EMI and 0.5 weight percent defoamer to the total amount of epoxy compound and acid anhydride curing agent to the epoxy compound and acid anhydride curing agent in the weight ratio shown in Table 3. The adhesive composition was applied to an area of 1.5 cm from the end in the vertical direction of a cycloolefin polymer plate or a stainless steel plate with a length x width x thickness of 10 cm x 2.5 cm x 10 mm. The same test piece was placed on top of the plate in the reverse direction and heated at 100°C for 15 hours to bond them. The adhesive strength was evaluated by a tensile test (room temperature, 5 mm per minute) using a multipurpose material testing machine (Imoto Manufacturing Co., Ltd. IMC-90FE type).
[0082] [Table 3]
[0083] As shown in Table 3, the cured products of Examples 10 to 13 had the same shear strength as the cured products of the glycidyl ethers of Comparative Examples 4 to 6.
[0084] (6) Adhesion test 2 Example 14 Two L-shaped stainless steel test pieces with a bonding area of 5 cm x 2.5 cm were bonded together at 100°C for 15 hours using an adhesive composition prepared in the same manner as in Example 10. The adhesive strength of the bonded T-shaped test pieces was evaluated by a tensile test (room temperature, 5 mm per minute) using a multipurpose material testing machine (IMC-90FE model, manufactured by Imoto Manufacturing Co., Ltd.). As a result, the bonded state was maintained even under the maximum load of 2000 N, and neither peeling nor destruction occurred.
Claims
1. The following general formula (Ia): 【Chemistry 1】 (In general formula (Ia), R 1 , R 2 , and R 3 are each independently a monovalent group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, and a phenyl group. A cured product of an epoxy compound having one or more glycidic acid ester groups represented by The method includes a step of immersing the material in an alkaline aqueous solution or a lipase-containing aqueous solution. Method for decomposing hardened materials.
2. The decomposition method according to claim 1 , wherein the epoxy compound has two or more glycidic acid ester groups.
3. The cured product is a cured product of a curable resin composition containing an amine-based curing agent or an acid anhydride curing agent. The decomposition method according to claim 1 or 2.
4. The decomposition method according to claim 3 , wherein the curable resin composition further contains a curing accelerator.
5. The decomposition method according to claim 3 or 4, wherein the cured product is obtained by heating the curable resin composition at 120°C or lower.
Citation Information
Patent Citations
Multi-active functional group coating fortifier and preparing method thereof
CN105821707A
Dye image receiving material and image forming method
JP1996058248A
Novel polyfunctional glycidic ester compound and production method thereof, and polymer prepared using the same
JP2015214497A
Water-absorbing resin crosslinking agent, absorbent and production method thereof
JP2016124995A
Reactive composition
JP2019196315A